The Effect of Boiling Time and Roasting Time With Clay Crock on The Quality of Roasted Durian Bean Chips - Yulia Ester Pakpahan; Zulkifli Lubis; Setyohadi Setyohadi (Universitas Sumatera Utara, 2014)
This research was conducted to find the effect of boiling and roasting time with clay crock on the quality of roasted durian bean chips. The research had been performed using factorial completely randomized design with two factors i.e of boiling time (A) : (10, 15, 20 and 25 minutes) and roasting time with clay crock (P): (2, 2.5, 3, and 3.5 minutes) . The parameters analyzed were yield, moisture content, ash content, protein content, fat content, carbohydrate content and organoleptic values (color, taste and crispness). The results showed that the boiling time had highly significant effect on yield, moisture content, fat content, protein content, carbohydrate content, organoleptic values of color, taste and crispness. Roast frying time with clay crock had highly significant effect on yield, moisture content, ash content, fat content, protein content, carbohydrate content, organoleptic values of color, taste and crispness. The interaction of the two factors had highly significant effect on yield, moisture content, ash content, fat content, protein content, carbohydrate content, organoleptic values of color, taste and crispness. The 25 minutes of boiling and 3,5 minutes of roasting gave the best quality of chips. Keywords : durian bean chips, boiling time and roasting time with clay crock.